Hybrid Nanofluids for Solar Thermal Process Heating Applications - Upadhyay S.; Chandra L.; Sarkar J. (My University, 2025)
Experiments with turbulent flow of hybrid nano-oils are reported to mitigate the dearth of experimental data for assessing the developed generalized Nusselt number correlation, deduced using separation approach. A controlled, Joule-type, uniform heating condition is adopted for simplicity. The significant findings are (a) the Nusselt number enhanced with the addition of nano-particles, (b) the addition of nanoparticles increases the pressure drop and (c) the assessment of Figure of Merit confirms that the use of hybrid nano-oil is beneficial compared to pure oil, and (d) the generalized Nusselt number correlations are applicable for hybrid nano-oils within the reported uncertainty of ± 15%. Therefore, the experiment is a step towards utilization of hybrid nano-oils as heat transfer fluid for heat transfer applications. © 2023. The Authors.